The Application of the Restorative Justice Approach In the Resolution of Criminal Cases Involving Violence Against Children Within the Jurisdiction of the Bali Provincial Police - Ni Komang Sri Rusmawati; Komang Edy Dharma Saputra (Journal Of Social Science (JoSS), 2026)
Violence against children is a serious problem that requires a response oriented not only toward punishing the perpetrator but also toward the rehabilitation of the victim. The restorative justice approach is an alternative model for resolving criminal cases that emphasizes restoring relationships between the perpetrator, victim, and community through dialogue, agreement, and shared responsibility. Within the jurisdiction of the Bali Provincial Police, the application of this approach has been increasingly used in handling cases of violence against children. This study examined the effectiveness of the restorative justice approach in resolving crimes of violence against children within the jurisdiction of the Bali Provincial Police, as well as identifying the factors that support and hinder its implementation. The research method used was empirical legal research with a qualitative approach. The results are expected to provide an overview of the extent to which the restorative justice approach is able to provide protection and rehabilitation for child victims, as well as create more effective case resolution compared to conventional criminal approaches.